PENGARUH CAPITAL INTENSITY TERHADAP TAX AGGRESSIVENESS DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - Teguh Erawati; Sri Mairani Julina (Jurnal Akuntansi Dan Manajemen, 2025)
This research aims to examine the effect of capital intensity on tax aggressiveness with corporate social responsibility as a moderating variable. The data used in this research is secondary data by taking samples from manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2018 - 2021 period. Sample selection was carried out using a purposive sampling method from 140 companies that went public and obtained 38 samples that met the requirements. The research results show that capital intensity has a positive effect on tax aggressiveness, but corporate social responsibility as a moderating variable cannot moderate the effect of capital intensity on tax aggressiveness.